Extraction Techniques Used for the Removal of Pharmaceuticals from Environmental Samples - Mustafa Soylak; Muhammed Saqaf Jagirani (Tabriz University of Medical Sciences, 2021)
The existence of pharmaceuticals in the ecosystem originating from human activities has to pay more scientific interest during the past decades due to the concerns about their joint ecological effects in flora and fauna and by the extent in human health. The capability to determine pharmaceuticals in an aqueous environment has been limited. Though, emerging methods are changing the pharmaceutical determination abilities and our understanding of their existence in the aqueous environment. Different modern analytical techniques such as spectroscopic and chromatographic methods have been used for the detection of pharmaceuticals from the ecosystem due to the trace level of these contaminates, they need sample preparation and pre-concentration methods such as solid-phase extraction, and microextraction extraction techniques have been used. These separation- pre-concentration methods are successfully applied for the selective and sensitive quantification of pharmaceuticals from the environmental samples.